Pemanfaatan Limbah Tulang Ikan (Rastrelliger kanagurta) sebagai Tepung Kalsium Tinggi - Nila Tanyela Berghuis; Ida Fitri Maharani; Cantika Samsrestu R; Rahmad Gunawan; Sri Wahyuni Siregar; Sherina Saskia; Alfiyah Qaulan (Stannum : Jurnal Sains dan Terapan Kimia, 2023)
Fish bones are one of the by-products of processing fish fillets. The yield produced from the process of making fish fillets produced is only about 36% and the remaining 64% is waste that is lost in each processing process. Fish bones consist of organic compounds and inorganic compounds (minerals). The waste generated from the fish processing industry has the highest calcium content in the fish body. From the point of view of food and nutrition, fish bones are very rich in calcium that humans need, because the main elements of fish bones are calcium, phosphorus, and carbonate. Thus, fish bone waste has great potential to be used as raw material for calcium-rich fish bone meals. In this study, the utilization of mackerel bones will be studied, so it is very important to know the formula for the best concentration of mackerel bone meal, to know the potential calcium content in mackerel bones. The characterization in this project is intended to determine and determine the experimental results quantitatively. The characterizations carried out in this study were atomic absorption spectrophotometer (AAS) to determine the levels of Ca, Fe, and Zn and UV-Vis spectrophotometer to determine phosphate levels in mackerel bones. The results of the average mineral levels of Zinc, Iron, and Calcium respectively were 32.425 mg/100 gr, 4.3 mg/100 gr, and 213.825 mg/100 gr. While the value of phosphate concentration in mackerel bone meal was 2784.116 ppm. This is following the standards of BPOM.